Cytopathological study of salivary gland lesions in rural population: Use of the Milan system for reporting - Dr. Bagwan Mahammadtalha; Dr. Sunil Y. Swami (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Salivary gland lesions are superficial lesions & seek attention of patient easily. These lesions vary from non-neoplastic to neoplastic ones and from benign to malignant. Impact of changing habits of people may be reflected in spectrum of oral health & lesions of salivary glands.Objectives and Method: Present study includes the spectrum of distribution of various lesions of salivary glands in the patients visiting tertiary care rural hospital. In the present study, the Milan system was used for reporting salivary gland cytopathology in 150 cases.Results: FNAC proved to be a safe and effective modality in diagnosis and planning management of patients with salivary gland lesionsin the rural based population.Conclusion: Milan system was found characteristically significant for cytopathological diagnosis of SGLs.